Characterization of odor emission on the working face of landfill and establishing of odorous compounds index. (August 2015) - Wenjing, Lu; Zhenhan, Duan; Dong, Li; Jimenez, Luis Miguel Caicedo; Yanjun, Liu; Hanwen, Guo; Hongtao, Wang
Highlights: Temporal variations of odor emission on the working face were investigated. Serious odor pollutions tend to happen at 2:00, 6:00 and 14:00 in a day. Major odor pollutant families are sulfur and oxygenated compounds. Index of odorous compounds on the working face was identified. Abstract: Temporal variation (seasonal and daily) of odor emission on the working face of a large sanitary landfill in China was characterized through a 2 yearlong case study. Odor pollution was most serious in spring and autumn, while lower odor concentrations were detected in summer and winter. The daily fluctuation of odor concentration on the working face showed that 2:00 am, 6:00 am, 2:00 pm and 10:00 pm were the "most probable times" for odor pollution occurrence, which deserves focused attention in odor control projects. Correlations analysis found that 41% of the variance in odor concentrations can be explained by the chemical concentrations of odorous compounds. Moreover, the selection criteria for the index of odorous compounds were also established by evaluating the odor concentration, contribution to odor strength and the frequency of each compound present in all the samples. Ethyl alcohol, α-piene, hydrogen sulfide, dimethyl sulfide, limonene, methyl mercaptan, dimethyl disulfide, and diethyl sulfide comprise the index of odorous compounds on the working face of typical municipal solid waste landfill in China.